2018
DOI: 10.3390/horticulturae4020011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Temperature and Potassium on Biomass and Quality of Dark Red ‘Lollo Rosso’ Lettuce

Abstract: Abstract:Lettuce is an economically important crop for small and medium-sized growers. When grown in adverse environmental conditions, lettuce is vulnerable to a deterioration of yield and quality. Research concerning the impact of elevated potassium (K) levels on leafy vegetables, such as lettuce, is lacking. Therefore, seeds of dark-red 'Lollo' lettuce were germinated under greenhouse conditions at 25/20 • C (day/night). Plants were transferred into 11-L containers and placed into growth chambers at 25 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
12
2
3
Order By: Relevance
“…While under high-temperature treatment, the index of flavonoids of basil decreased considerably. These findings contradict many studies [31,38,39] because increased flavonoids are usually associated with thermophilic plant defense mechanisms against heat stress. Moreover, increased growth temperature from 30/22 • C to 38/30 • C for basil under elevated CO 2 produced more Anth content.…”
Section: Discussioncontrasting
confidence: 86%
“…While under high-temperature treatment, the index of flavonoids of basil decreased considerably. These findings contradict many studies [31,38,39] because increased flavonoids are usually associated with thermophilic plant defense mechanisms against heat stress. Moreover, increased growth temperature from 30/22 • C to 38/30 • C for basil under elevated CO 2 produced more Anth content.…”
Section: Discussioncontrasting
confidence: 86%
“…Conversely, there were higher concentrations of Fe in waterlogged roots of stressed plants (Smethurst et al 2005).To the best of our knowledge, there are no studies yet that have looked at the combined effect of waterlogging and eCO 2 and their influence on plant nutritional quality, two conditions that are likely to interact in the future. Sublett et al (2018) studied the consequence of eT (+8°C) on lettuce in a greenhouse experiment, and found a decrease in leaf Mg, K, Ca Mn and Mo concentrations. When looking at temperature and eCO 2 , it was shown that the combination of both factors may restore soybean (Köhler et al 2018) and wheat (Asif et al 2019) seed Fe and Zn concentrations to levels obtained under ambient CO 2 (aCO 2 ).…”
Section: The Effects Of Other Climate Change Factors On Nutrient Accumentioning
confidence: 99%
“…The colour variety of leafy greens can easily be increased by incorporating red leaves, such as the dark red (one might almost say purple) of Lollo Rosso. This the more colourful version of the pale green Lollo Bionda (Sublett, Barickman, & Sams, 2018). There are, in fact, a number of popular red lettuce cultivars, including "New Red Fire Lettuce", "Red Sails Lettuce", "Redina Lettuce", "Galactic Lettuce", and the "Benito Lettuce".…”
Section: Leafy Greens: a Sensorial Analysismentioning
confidence: 99%